The earthquake experience. Philosophy of catastrophe and Italian thought - Tagliapietra, Andrea (Scenari, 2021)
The word catastrophe indicates the experience of a sudden and disastrous change in the state of things. Earthquakes show us the authentic face of catastrophe as an experience of being at the mercy of a appaling event, chaotic and, although scientifically explained today in its causes, still unpredictable and, therefore, ultimately random. Thus the catastrophe, beyond the answers of science, develops a radical, authentically philosophical question, that of the meaning and order of the whole. The essay examines the reactions of philosophical thought to the event of the 1755 Lisbon earthquake and the difference between European and Italian thought in the construction of a philosophy of catastrophe.